2013
DOI: 10.1103/physreva.87.063832
|View full text |Cite
|
Sign up to set email alerts
|

Dark solitons in nonlocal media with competing nonlinearities

Abstract: We investigate analytically and numerically the propagation properties of dark solitons in nonlocal media with competing nonlinearities. We obtain analytical relations for soliton parameters for an arbitrary degree of nonlocality. In particular, we show that the velocity of dark solitons can be affected by the degree of nonlocality of competing nonlinearities. The analytical results are confirmed by direct numerical simulations of the full model describing propagation of dark solitons in nonlocal media with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The positive and negative signs of the index α 2 represent the competing self-focusing and self-defocusing nonlinearities, respectively. It has also been shown that the stationary dark soliton solution always exists if α 1 + α 2 < 0 [68,72].…”
Section: Interaction Between Dark Solitons In Weakly Nonlocal Mediamentioning
confidence: 97%
See 3 more Smart Citations
“…The positive and negative signs of the index α 2 represent the competing self-focusing and self-defocusing nonlinearities, respectively. It has also been shown that the stationary dark soliton solution always exists if α 1 + α 2 < 0 [68,72].…”
Section: Interaction Between Dark Solitons In Weakly Nonlocal Mediamentioning
confidence: 97%
“…We should emphasize that (16) describes exactly the dark solitons in media with competing nonlocal cubic nonlinearities obtained previously [72].…”
Section: Dark Solitons Interactions With General Nonlocal Casementioning
confidence: 97%
See 2 more Smart Citations
“…The competing nonlinearities of media induced by different physical processes contribute to the overall nonlinear response, for example, simultaneous local and long range interaction in Bose-Einstein condensation [33], and thermal and orientational nonlinearities in nematic liquid crystal [31,34]. The competing nonlocal nonlinearities have profound effect on the formation of novel solitons' states [35][36][37][38][39][40] and the interactions of bright and dark solitons [41,42]. Besides the model with synthetic double nonlocal nonlinearities [31,[37][38][39][40][41][42], the competing effect between local and nonlocal nonlinearities has also drawn considerable attention [43][44][45][46][47][48][49][50][51][52] in both optics and Bose-Einstein condensates.…”
Section: Introductionmentioning
confidence: 99%